The Evaluation of Melatonin Effect Against The Early Effect of Ionizing Radiation Induced Lung Injury - raziyeh tahamtan; gholam hassan haddadi; ali reza tavassoli (Fasa University of Medical Sciences, 2014)
Background & Objective: Lung is a radiosensitive organ. Patients who are undergoing radiation therapy in their chest are subjected to radiation pneumonitis in the early phase and pulmonary fibrosis in the late one. Melatonin scavenges free radicals directly and acts as an indirect antioxidant through the activation of major antioxidant enzymes as well. The aim of the study thus is to investigate the effect of melatonin against the early damages in irradiated lungs. Materials & methods: Male wistar rats were divided into five groups: the first group was considered as the control group. Both the second and the third group received 100 mg/kg melatonin intraorally however, the latter one underwent through 18Gy radiotherapy as well. The fourth group underwent through 18Gy radiotherapy in their chests. After 48 hours, all of the rats were killed for histhopathological evaluation. Results: the results indicated that radiation increases the collapse and fibrosis and cause the abundance of macrophage compared to control group (p<0.05). Oral administration of melatonin before radiation therapy significantly increased the lymphocyte and macrophage frequency (p<0.001) and decreased the RBC (p<0.05) frequency compared to the radiation group. Conclusion: According to the results, melatonin can prevent early damages in irradiated lungs. Free radicals cause cytotoxicity and melatonin can directly decrease the radiation induced cell damages by converting the free radicals to non- toxic compounds and also through the activation of the major antioxidant enzymes.